Etiology and Epidemiology of Travelers’ Diarrhea among US Military and Adult Travelers, 2018–2023 - Melissa S. Anderson; Evelyn W. Mahugu; Hayley R. Ashbaugh; Aaron G. Wellbrock; Maia Nozadze; Sanjaya K. Shrestha; Giselle M. Soto; Rania A. Nada; Prativa Pandey; Mathew D. Esona; Daniel J. Crouch; Michelle Hartman-Lane; et al. (Emerging Infectious Diseases)
Travelers’ diarrhea has a high incidence rate among deployed US military personnel and can hinder operational readiness. The Global Travelers’ Diarrhea study is a US Department of Defense–funded multisite surveillance effort to investigate the etiology and epidemiology of travelers’ diarrhea. During 2018–2023, we enrolled 512 participants at partner institutions in 6 countries: Djibouti, Georgia, Egypt, Honduras, Nepal, and Peru. Harmonized laboratory methods conducted at each partner institution identified >1 pathogens, including Escherichia coli (67%–82%), norovirus (4%–29%), and Campylobacter jejuni (2%–20%), in 403 (79%) cases. Among cases, 79.7% were single infections, 19.6% were double infections, and 0.7% were triple infections. The most common enterotoxigenic E. coli colonization factors identified were CS3 (25%) and CS21 (25%), followed by CS2 (18%) and CS6 (15%). These data can inform best treatment practices for travelers’ diarrhea and support US military health readiness.